Computed tomographic appearance of sialoceles in 12 dogs. Issue 1 (28th September 2021) - Oetelaar, Garrett Swann; Heng, Hock Gan; Lim, Chee Kin; Randall, Elissa
Abstract: Published findings on the computed tomographic (CT) appearance of sialoceles are limited to brief descriptions from reported cases in eight dogs and one cat. The authors have seen sialoceles with CT characteristics that are not consistent with these previous reports. The purpose of this multicenter, retrospective, descriptive, case series study was to provide more detailed descriptions of the CT appearance of confirmed sialoceles in dogs. Dogs over a 10‐year period with cytologically or histologically confirmed sialoceles and pre‐ and postcontrast CT studies of the head were included. Multiple qualitative and quantitative features were described for each sialocele with histological correlation. Twelve dogs with a total of 13 sialoceles were identified, including: seven cervical sialoceles, three complex (combined cervical and sublingual) sialoceles, two sublingual sialoceles, and one zygomatic sialocele. All sialoceles were characterized by fluid attenuating, non‐contrast enhancing contents (median 18.5 HU) and soft tissue attenuating, contrast‐enhancing walls. The external margins of all sialocele walls were smooth; however, the internal margins in six sialoceles were irregular with poorly defined nodular to frond‐like protrusions. Mineralized foci of variable size (range < 1 mm to 4.8 mm) and attenuation (range 119 to 1253 HU) were present in seven sialoceles and histologically identified as sialoliths (three sialoceles) and osseous metaplasia (two sialoceles). A unique finding in the sialoceles in this study was the presence of intraluminal nodular to frond‐like protrusions arising from the wall. This study also reports the CT appearance of cervical and complex sialoceles and sialocele mineralizations.